Community Participation in Increasing Children’s Attendance in Quality Primary Education in Lao PDR: A Case Study of BNC project - MAHAPHOM , Somphien (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Recognition of the importance of education to national development has led to the implementation of many educational development programmes, which aim at improving access to education for all children in Lao PDR. One programme that focuses on primary education initiatives is Basic Education Quality and Access in Lao PDR [BEQUAL]. This research evaluated the level of community participation in the BEQUAL NGO Consortium [BNC] project in increasing children’s attendance in quality primary education. Using a qualitative research approach (including non-participant observation, communicative ecology mapping, in-depth semi-structured interviews, focus groups and documentation), it analysed how effective the community participation is, in the implementation of the BNC project. The interviews and focus groups involved 13 participants from three different groups engaged with by the BNC: local primary school teachers, parents of school children and BNC staff. Findings revealed that all community members highly appreciated the project intervention, although the level of their participation was low. Positive change in children’s learning, parents’ awareness about the importance of education to their child’s life and understanding of how parenting skills affects their child’s education were claimed to be key benefits experienced by members of the community. The findings also revealed that in general community members have passive attitudes towards the development project, in the sense that they wait for assistance from donors. To address this issue, it is recommended that BNC could increase the level of participation by empowering all primary stakeholders (community leaders, teachers, village volunteers and parents) to participate in the process of problem identification, problem solving, and decision making. It is also recommended that BNC could consider teachers, parents and village volunteers as agents of change for their own community as evidence indicates that these three groups can play a significant role in addressing the level of school attendance in their community.